Emerging strategies for the synthesis of monodisperse colloidal semiconductor quantum rods - Jia, Guohua; Xu, S.; Wang, A. (R S C Publishing, 2015)
Colloidal semiconductor quantum rods are exciting materials from both fundamental and technological points of view. The electronic and optical properties of these materials are governed by the decrease in the confinement of charge carriers along the long axis and by the cylindrical symmetry of the particles. Their intrinsic properties, such as highly controlled optical characteristics, are advantageous in biological labeling, photovoltaic devices and light emitting diodes. Thanks to the advances in the development of strategies for synthesizing colloidal semiconductor quantum rods that made these materials available. The availability of colloidal semiconductor quantum rods provides a platform for both the investigation of their stimulating properties and the exploration of their promising applications. This review article focuses on the recent advances in the strategies for the synthesis of monodisperse colloidal semiconductor quantum rods. The fundamental issues associated with the anisotropic growth of colloidal nanocrystals such as facet, surface energy, selective binding of the surfactant, growth kinetics and thermodynamics were addressed, interpreted and discussed. Synthetic strategies for colloidal semiconductor quantum rods, being different from one another, were introduced and the growth mechanisms were revealed. The progress on the synthetic strategies of colloidal semiconductor quantum rods provided the basis for many inspiring applications in the fields of photocatalysis, opto-electronic devices, bio-labeling and other advanced applications.